Nonclassic congenital adrenal hyperplasia misdiagnosed as Turner syndrome - Mishra, Vineet V. (J Hum Reprod Sci, 2015)
We present a patient with nonclassic congenital adrenal hyperplasia (NCAH) misdiagnosed as mosaic Turner syndrome. She presented with complaints of primary infertility. Short stature, the presence of facial hair and hoarse voice was also noted. She had primary amenorrhea and was advised for karyotype at 16 years of age, which was reported as 45, X[20]/46, XX[80], stating her as a case of mosaic Turner syndrome. Clitoroplasty was done at 21 years of age for clitoromegaly, which was noticed during puberty. The diagnosis of mosaic Turner could not explain the virilization. Therefore, we repeated the karyotype, which revealed 46, XX in more than 100 metaphases and was sufficient to exclude mosaicism. Furthermore, the endocrinological evaluation revealed high testosterone level with a normal 17 alpha-hydroxyprogesterone (17-OHP). The presence of pubertal onset virilization with a karyotype of 46, XX and raised testosterone level with normal 17-OHP level, raised the suspicion of NCAH for which adrenocorticotropic hormone stimulation test was done which confirmed the diagnosis of NCAH.